Kinetic Parameters Investigation for The Esterification of Free Fatty Acid from Coconut Oil Mill Waste using Montmorillonite-Sulfonated Carbon from Glucose Composite Catalyst - Hasanudin Hasanudin; Wan Ryan Asri; Widia Purwaningrum; Fahma Riyanti; Novia Novia; Roni Maryana; Muhammad Al Muttaqii (Molekul, 2022)
Coconut oil mill waste (CMW) contained high free fatty acid (FFA) content which potentially could be converted into a value-added product such as fatty acid methyl ester (FAME). In this study, a montmorillonite-sulfonated carbon catalyst was used to evaluate the kinetic parameter of FFA conversion from CMW into FAME. The characterization of FTIR and SEM-EDX confirmed that the -SO3H groups were successfully incorporated into montmorillonite- carbon catalyst. The highest catalyst acidity (9.4 mmol/g) was achieved by a ratio of montmorillonite to sulfonated carbon of 1:3 % w/w. The kinetic study using montmorillonite-sulfonated carbon 1:3 % w/w showed that the reaction temperature and molar ratio of methanol to FFA (% v/v) were positively correlated to the reaction rate. The highest rate constant of esterification towards the product (k1), reactant (k2), and equilibrium were 0.1187, 0.0595, and 1.995, achieved by a temperature of 80 ˚C, respectively. The Arrhenius constant and activation energy towards the product were 3.3085×106 and 50.3 J/mole, respectively. The reaction temperature was positively correlated to the equilibrium constant, which indicated that the reaction was endothermic. The kinetic model validation revealed that the predicted value from the model was adequately in accordance with the experimental value, as indicated by a high coefficient of determination.